Construction of cyclic enones via gold-catalyzed oxygen transfer reactions - Liu, Leping; Xu, Bo; Hammond, Gerald B. (Beilstein Journal of Organic Chemistry, 2011)
During the last decade, gold-catalyzed reactions have become a tour de force in organic synthesis. Recently, the gold-, Brønsted acid- or Lewis acid-catalyzed oxygen transfer from carbonyl to carbon–carbon triple bond, the so-called alkyne–carbonyl metathesis, has attracted much attention because this atom economical transformation generates α,β-unsaturated carbonyl derivatives which are of great interest in synthetic organic chemistry. This mini-review focuses on the most recent achievements on gold-catalyzed oxygen transfer reactions of tethered alkynones, diynes or alkynyl epoxides to cyclic enones. The corresponding mechanisms for the transformations are also discussed.
Keywords: alkyne–carbonyl metathesis; cyclic enones; gold-catalyzed; oxonium; oxygen transfer